Adaptive method with noise- and signal-dependent switching of filters for suppression of non-stationary noise in an electrocardiogram signal in real time - Tulyakova, N.O.; Trofymchuk, O.M.; Stryzhak, O.Ye. (Radiotekhnika, 2018)
А new method for suppressing non-stationary noise in an electrocardiogram (ECG) in real time with a noise- and signal-dependent switching of filter with the most suitable processing of local signal segment is proposed. Adaptive algorithms are designed on the basis of this method. Statistical estimates of efficiency are obtained using such criteria as mean-square error, maximum absolute deviation, and signal-to-noise ratio for a model of ECG signal sampled at 1 kHz under conditions of different levels of additive Gaussian noise. It is shown that, with a very low noise level, the proposed algorithms do not distort the QRS-complex, and with a middle and high noise level, they provide a high degree of its suppression. In comparison with the modern dynamic algorithm of filtering of electromyographic (EMG) noise in an ECG, the proposed adaptive filters have an advantage in efficiency and smaller processing delay. Good quality of suppression of different levels of EMG noise in the ECG signal is demonstrated.